SAT0002 Free Fatty Acids Promote an Inflammatory Profile in Osteoblasts. (9th June 2015) - Frommer, K.W.; Schäffler, A.; Lange, U.; Rehart, S.; Müller-Ladner, U.; Neumann, E.
Abstract : Background: Chronically elevated free fatty acid (FFA) levels are associated with numerous inflammatory cardiovascular and metabolic diseases such as atherosclerosis, coronary heart diseases and type 2 diabetes. This pathophysiological link to inflammation could also be found in vitro with different cell types. However, the influence of FFA on cells of bone metabolism is largely unknown so far. Obesity is associated with a higher risk of osteoarthritis also in non-weight bearing joints and increased amounts of visceral fat are associated with lower bone density. This suggests that FFA may also play a role in bone metabolism. Objectives: To test this hypothesis, we analyzed the effect of FFA on cells of bone metabolism in the context of rheumatic diseases. Methods: Primary osteoblasts were isolated from cancellous bone of rheumatoid arthritis (RA) or osteoarthritis (OA) patients undergoing knee joint surgery. The osteoblasts were stimulated with saturated and unsaturated FFA of different length. Immunoassays were used to quantify protein secretion. mRNA expression levels were quantified by real-time PCR. Results: Stimulating osteoblasts with FFA increased the secretion of the proinflammatory cytokine IL-6 and the chemokine IL-8 in a donor-dependent manner. While certain osteoblast populations showed a strong response to FFA (IL-6: up to 9.1-fold increase; IL-8: up to 221-fold increase), others responded to a much lower degree. RANKL and OPG, important regulators of osteoclastogenesis and osteoclast activity, were not affected by FFA on protein as well as mRNA level. mRNA expression of osteoblast activity markers (ALP and collagen type I), markers of osteoblast differentiation (SOX9, RunX2, osterix, osteocalcin), and Wnt signaling molecules (axin-2 and β-catenin) also remained unchanged by FFA stimulation. Interestingly, both saturated and unsaturated FFA caused a pro-inflammatory response in osteoblasts. Conclusions: Inflammation plays a key role in many rheumatic diseases and increased inflammatory activity is associated with decreased bone density. Hence, locally increased FFA levels may promote inflammation as well as indirectly the inflammation-mediated degradation of bone in rheumatic diseases. However, FFA appear not to affect osteoblast function directly. Disclosure of Interest: None declared